صناعة المجتهد بين التراث والمعاصرة (Producing Mujtahid between Tradition and Contemporary) - ميثاء سعيد عبداالله الخاطري; سيد إسكندر شاه; حسام الدين الصيفي (Journal of Islam in Asia (E-ISSN 2289-8077), 2019)
من روائع هذا الموروث الديني عن النبي ﷺ، قدرته على مسايرة الحوادث والمستجدات، واستيعاب التنوع والاختلاف الزماني والمكاني والأحوال، بحيث لا يند عن النص أو فهمه شيء. الاجتهاد من فروض الكفاية التي لا يجوز أن يخلو منه عصر، ومن تنادى بإغلاق باب الاجتهاد فقد أخطأ، باب الاجتهاد لا يوصد لأن مسائل العصر متجددة، والنوازل كثيرة، وخاصة في هذا الزمان المتسارع، وإن قل الاجتهاد الفردي إلا أن الاجتهاد الجماعي له دور كبير في إيجاد الحلول التي تحتاجها الأمة. هذا البحث يهتم بصناعة المجتهد، والعناية بإخراج مجتهدين مؤهلين للعملية الاجتهادية، أو الفتيا، وفق شروط المجتهد التأهيلية. خلص البحث إلى النتائج الآتية: الاهتمام بالشخصية المختارة للصناعة البحثية، وإعداد الاختبارات والمقابلات المنتقاة بدقة عالية لاجتيازها، وتخطي العقبات والتحديات والعناية بالمنظومة التعلمية المهمة في صناعة المجتهد، والاهتمام بالتراث الإسلامي في الاستفادة منه والبناء عليه، واستصحابه بالقدر الذي يكون معينا للوصول للمطلوب. الكلمات المفتاحيّة: الاجتهاد، المجتهد، التراث، الموروث الإسلامي. Abstract Among the masterpieces of religious tradition of Prophet S.A.W. is the ability to cope with the events and developments and to absorb the diversity of temporal and spatial conditions, in line with the Islamic verses. Ijtihad is the duties of sufficiency that ones have to bear them. Therefore, whoever intends to close the door of Ijtihad has erred, since the issues of mankind changeable from day to day. Although there are small number of Ijtihad individually but there are Ijtihad collectively that played big role in finding solutions which arise among people. This study discussed the issues of producing Mujtahid, in terms of qualification and youthness, according to the stipulated conditions. The study found that it is important to have selection of qualified person to become mujtahid as well as the selected tests and interviews with high accuracy, so that they could overcome the obstacles and challenges later. The study also found that there should have a concern on the important learning system in producing mujtahid and the Islamic heritage as well. Keywords: Ijtihad, Mujtahid, Tradition, Islamic Tradition.